Toward a Model of Explaining between Inspirational Motivation, Intellectual Stimulation on Employees’ Innovative Behaviour with Job Engagement as a Mediating - Jadu, Khaled; Mustapa, Zuhaina; Omar, Nor Farehan; Razak, Norfadzilah Abdul (International Review of Management and Marketing, 2026)
Organizations heavily rely on the innovative behaviours of their employees and, therefore, need to remain competitive with respect to their rapidly transforming environments. Inspiring motivation and intellectual stimulation of employees with regard to behavioural transformations is the primary focus of transformational leadership. The purpose of this study is to examine the impact of dimensions of transformational leadership, inspirational motivation and intellectual stimulation, on employees’ innovative behaviours, with mediating role of job engagement. Using a statistical technique, Partial Least Squares Structural Equation Modelling (PLS-SEM), information was gathered from 351 employees from three telecommunications companies in Jordan and a quantitative methodology was used in the analysis. The results found positive relationship between inspirational motivation, intellectual stimulation and employees’ innovative behaviours, while transformational leadership dimensions influence on job engagement. In addition, it was found that job engagement partially mediated the relationships, meaning that employees, especially in relation to engagement, are more likely to act upon the innovative behaviours to demonstrate leadership on the work role. The predictor of these relationships was intellectual stimulation, demonstrating the importance of developing a culture that promotes problem-solving and innovative thinking. The present research adds to inspiring motivation and intellectual stimulation literature by demonstrating and clarifying ways to promote innovation behaviour through transformational leadership, and offers a useful instrument for organizations in their attempts to enhance and strengthen job engagement and innovation performance.